2008
DOI: 10.1088/0143-0807/29/3/024
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a GUM-compliant course for teaching measurement in the introductory physics laboratory

Abstract: An evaluation of a course aimed at developing university students' understanding of the nature of scientific measurement and uncertainty is described. The course materials follow the framework for metrology as recommended in the Guide to the Expression of Uncertainty in Measurement (GUM). The evaluation of the course is based on responses to written questionnaires administered to a cohort of 76 first year physics students both pre-and post-instruction, which were interpreted in terms of 'point' or 'set' reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 25 publications
(43 reference statements)
1
27
0
4
Order By: Relevance
“…As with any other aspect of physics teaching and learning, it is possible for students to navigate their way through their laboratory course by relying on surface ͑rote͒ learning of procedures unless students have opportunities to discover that their mental models of scientific measurement may not necessarily be appropriate in the scientific context. A recent evaluation 31 of our course based on the probabilistic framework has shown that we have been significantly more successful in the development of an appropriate conceptual framework of uncertainty in scientific measurement.…”
Section: Discussionmentioning
confidence: 99%
“…As with any other aspect of physics teaching and learning, it is possible for students to navigate their way through their laboratory course by relying on surface ͑rote͒ learning of procedures unless students have opportunities to discover that their mental models of scientific measurement may not necessarily be appropriate in the scientific context. A recent evaluation 31 of our course based on the probabilistic framework has shown that we have been significantly more successful in the development of an appropriate conceptual framework of uncertainty in scientific measurement.…”
Section: Discussionmentioning
confidence: 99%
“…There is much research demonstrating the effectiveness of labbased pedagogies at developing skills such as evaluating data and models, dealing with uncertainty and variability in data, and designing experiments [45][46][47][48][49][50].…”
Section: Midterm Exammentioning
confidence: 99%
“…For courses where skills development is the primary focus, students' performance on tests of conceptual mastery becomes less important than practical assessments of students' ability to, for example, make measurements and collect and interpret accurate data [3,10]. With a few exceptions [11,12], research-based assessments of students' laboratory skills are virtually nonexistent in the literature around laboratory course instruction.…”
Section: Introductionmentioning
confidence: 99%